Justification of the use of critical technologies in the agriculture on the basis of foresight design methodology - Tkachuk, Oleksandr (Management and Entrepreneurship: Trends of Development, 2020)
The article considers the results of using the method of critical foresight technologies in relation to the agricultural sector at the regional level, considering the region as a subject of competitive processes in the context of globalization. The purpose of the study is to determine the critical technology in the agro-industrial complex at the regional level, capable of implementing the final phase of Foresight to affect the industry, markets, environment and ultimately - the competitiveness of the region. Outlining the scope of foresight, the author considers the following key issues in this area, which are: agri-environmental condition of land, social issues - job creation in rural areas, ensuring food production for the population, necessary for medical standards and affordable prices. The research of foresight is focusing on the trends of innovation in the field of science and technology. The results of research have shown that the technology of grazing dairy herds can become a critical technology, a potential factor in the revival of animal husbandry in the region. This approach will solve the problem of maintaining soil fertility as a key competence in the development of the region’s agricultural and industrial complex, necessary for high yields of crops, and will solve social problems with job creation, providing food in accordance with medical standards, dairy market development. JEL Classification: C53, Q24, O13